Health Technology Assessment of Belimumab: A New Monoclonal Antibody for the Treatment of Systemic Lupus Erythematosus. (17th August 2014) - Specchia, Maria Lucia; de Waure, Chiara; Gualano, Maria Rosaria; Doria, Andrea; Turchetti, Giuseppe; Pippo, Lara; Di Nardo, Francesco; Capizzi, Silvio; Cadeddu, Chiara; Kheiraoui, Flavia; Iaccarino, Luca; Pierotti, Francesca; et al.
Abstract : Objective. Systemic lupus erythematosus (SLE) is treated with anti-inflammatory and immunosuppressive drugs and off-label biologics. Belimumab is the first biologic approved after 50 years as an add-on therapy for active disease. This paper summarizes a health technology assessment performed in Italy. Methods. SLE epidemiology and burden were assessed using the best published international and national evidences and efficacy and safety of belimumab were synthesized using clinical data. A cost-effectiveness analysis was performed by a lifetime microsimulation model comparing belimumab to standard of care (SoC). Organizational and ethical implications were discussed. Results. Literature review showed that SLE affects 47 per 100, 000 people for a total of 28, 500 patients in Italy, 50% of whom are affected by active form of the disease despite SoC. These patients, if autoantibodies and anti-dsDNA positive with low complement, are eligible for belimumab. SLE determines work disability and a 2–5-fold increase in mortality. Belimumab with SoC may prevent 4, 742 flares in three years being cost-effective with an incremental cost-effectiveness ratio of €32, 859 per quality adjusted life year gained. From the organizational perspective, the development of clear and comprehensive clinical pathways is crucial. Conclusions. The assessment supports the use of belimumab into the SLE treatment paradigm in Italy.